DNA sensors are expressed in astrocytes and microglia in vitro and are upregulated during gliosis in neurodegenerative disease - CUNNINGHAM, COLM; BOWIE, ANDREW; DUNNE, AISLING; COX, DONAL (My University, 2015)
The detection of nucleic acids by the innate immune system is an essential host response during viral infection. In recent years, a number of immune sensors capable of recognizing cytosolic DNA have been identified and include the PYHIN family members AIM2, IFI16, and p204 as well as the enzyme, cGAS. Activation of these receptors leads to the induction of antiviral genes including Type-1 interferons and chemokines such as CCL5. We have carried out extensive expression profiling of these DNA sensors and other members of the PYHIN family in highly purified primary astrocytes and microglia and have demonstrated that both cell types express the majority of these proteins at the mRNA level. In microglia, several family members are highly upregulated in response to IFN-β treatment while both cell types induce robust proinflammatory and antiviral cytokine production (e.g., IL-6, CCL5, IFN-β) in the presence of immune stimulatory DNA and RNA. The production of IL-6 is partially dependent on the interferon receptor as is IFN-β itself. Furthermore, we have found that p204 and AIM2 are upregulated in a Type I IFN dependent fashion in vivo, in a murine model of chronic neurodegeneration. Given the propensity of inflammatory responses to cause neuronal damage, increased expression and activation of these receptors, not only during viral infection but also during sterile inflammatory responses, has the potential to exacerbate existing neuroinflammation leading to further damage and impaired neurogenesis. GLIA 2015;63:812–825
PUBLISHED
Keywords: nucleic acids; nucleic acids